Optical flow structure effects in children's postural control - Godoi, Daniela; Barela, José A. [UNESP] (Public Library of Science (PLoS), 2016)
The aim of this study was to investigate the effect of distance and optic flow structure on visual information and body sway coupling in children and young adults. Thirty children (from 4 to 12 years of age) and 10 young adults stood upright inside of a moving room oscillating at 0.2 Hz, at 0.25 and 1.5 m from the front wall, and under three optical flow conditions (global, central, and peripheral). Effect of distance and optic flow structure on the coupling of visual information and body sway is age-dependent, with 4-year-olds being more affected at 0.25 m distance than older children and adults are. No such difference was observed at 1.5 m from the front wall. Moreover, 4-year-olds' sway was larger and displayed higher variability. These results suggest that despite being able to accommodate change resulting from varying optic flow conditions, young children have difficulty in dodging stronger visual stimuli. Lastly, difference in sway performance may be due to immature inter-modality sensory reweighting.